Guide to postproduction for TV and film : managing the process - Clark, Barbara, 1959- (Focal Press, 2002)
Are you an associate producer who needs to juggle projects and vendors while keeping on top of the latest trends and formats? Or an independent filmmaker who can't afford a misstep in the crucial postproduction phase? Take a step back and get a clear overview of the process. This guide will show you how to navigate each step in taking a TV or film project from production to final delivery. Start by getting a handle on the critical issues of budgets and schedules. From there, you'll learn the smoothest way to manage dailies, sound, editing, and completion. Detailed instructions and checklists f.